Produksi dan Komposisi Susu Kambing Peranakan Ettawa Melalui Pemberian Ekstrak Meniran - Puji Astuti; Heru Suripta; NE Sukarini (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2017)
This research was conducted to determine the difference in quantity and quality (specific weight, fat, protein, total solid, total solid non fat, fatty acid omega 6 and 3) of milk in ettawa goat fed meniran extract (Phyllanthus niruri). Experimental animals used in this study were 12 peranakan ettawa goat that were producing at the second lactation with average body weight of 50 kg and milk production about 1-2 liters. They were divided into four groups, each groups containing 3 animal. Group 1 (without meniran extract), group 2 (50 mg meniran extract/kg body weight), group 3 (100 mg meniran extract/kg body weight), and group 4 (150 mg meniran extract/kg body weight). Quality of milk calculated at the end in research and quantity of milk calculated every day twice a day in the morning and evening. The data obtained in the study were analyzed with ANOVA. The results showed there were significant difference (p<0,05) in feed consumption, milk quantity, but not at milk quality (specific weight, protein, total solid non fat) of Peranakan ettawa goat fed meniran extract. Key word : Peranakan ettawa goat, milk quantity dan quality, meniran extract